Be3Ru: Polar Multiatomic Bonding in the Closest Packing of Atoms. Issue 6 (21st June 2022) - Agnarelli, Laura; Prots, Yurii; Schmidt, Marcus; Krnel, Mitja; Svanidze, Eteri; Burkhardt, Ulrich; Leithe‐Jasper, Andreas; Grin, Yuri
Abstract: The new phase Be3 Ru crystallizes with TiCu3 ‐type structure (space group Pmmn (59), a =3.7062(1) Å, b =4.5353(1) Å, c =4.4170(1) Å), a coloring variant of the hexagonal closest packing ( hcp ) of spheres. The electronic structure revealed that Be3 Ru has a pseudo‐gap close to the Fermi level. A strong charge transfer from Be to Ru was observed from the analysis of electron density within the Quantum Theory of Atoms in Molecules (QTAIM) framework and polar three‐ and four‐atomic Be−Ru bonds were observed from the ELI−D (electron localizability indicator) analysis. This situation is very similar to the recently investigated Be5 Pt and Be21 Pt5 compounds. The unusual crystal chemical feature of Be3 Ru is that different charged species belong to the same closest packing, contrary to typical inorganic compounds, where the cationic components are located in the voids of the closest packing formed by anions. Be3 Ru is a diamagnet displaying metallic electrical resistivity. Abstract : The crystal structure of Be3 Ru is described as a 'coloring' variant of the hexagonal closest packing of spheres. This "metallic character" goes along with the low number of electrons in the last shell per atom (ELSA). In contrast to the typical intermetallic compounds, the electronic density of states of Be3 Ru shows a pseudo‐gap in the vicinity of the Fermi level.